2016
DOI: 10.3847/0004-637x/818/2/200
|View full text |Cite
|
Sign up to set email alerts
|

Global Modeling of Nebulae With Particle Growth, Drift, and Evaporation Fronts. I. Methodology and Typical Results

Abstract: We model particle growth in a turbulent, viscously evolving protoplanetary nebula, incorporating sticking, bouncing, fragmentation, and mass transfer at high speeds. We treat small particles using a moments method and large particles using a traditional histogram binning, including a probability distribution function of collisional velocities. The fragmentation strength of the particles depends on their composition (icy aggregates are stronger than silicate aggregates). The particle opacity, which controls the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
147
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(155 citation statements)
references
References 167 publications
(350 reference statements)
8
147
0
Order By: Relevance
“…They found that while erosion-limited growth of icy aggregates can easily produce aggregates with the right Stokes number for streaming instability, the mass loading in the disk midplane is too low in large parts of the disk. Estrada et al (2016) performed global simulations of dust growth in protoplanetary disks. While they took detailed physics into account, such as condensation fronts and a collision model comparable to ours, porosity was not considered.…”
Section: Implications For Comet Formationmentioning
confidence: 99%
“…They found that while erosion-limited growth of icy aggregates can easily produce aggregates with the right Stokes number for streaming instability, the mass loading in the disk midplane is too low in large parts of the disk. Estrada et al (2016) performed global simulations of dust growth in protoplanetary disks. While they took detailed physics into account, such as condensation fronts and a collision model comparable to ours, porosity was not considered.…”
Section: Implications For Comet Formationmentioning
confidence: 99%
“…On the other hand, local pressure maxima may be created in the disc at some locations by internal processes (e.g. Ruge et al 2016;Estrada et al 2016;Béthune et al 2016;Gonzalez et al 2017). These pressure bumps are privileged locations for planetesimal formation since they concentrate dust (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, most other mechanisms that have been proposed to bypass those barriers that have not been ruled out by numerical study (Estrada et al 2016) are inconsistent with the volatile abundances of the terrestrial planets in the Solar System (Flynn et al 2013;Marty et al 2013). This thermal processing seems likely to take two forms depending on the host disk dynamics, and those forms would set the planetary system architecture in an in situ planet formation scenario.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent epic endeavor Estrada et al (2016) verified that the problem persists even taking into account lucky grains (Windmark et al 2012;Garaud et al 2013). In this section we quickly sketch how large modifications to our understanding would be required to allow dry silicates to form planetesimals.…”
Section: Statement Of the Difficultymentioning
confidence: 99%
See 1 more Smart Citation